Problematika Pembelajaran Daring di Masa Pandemi Covid-19 Ditinjau dari Sudut Pandang Mahasiswa - Sukiman Sukiman (Educatio, 2022)
This study aims to discover online learning problems amid the covid-19 pandemic. The method used is descriptive qualitative with a phenomenological approach. The research subjects were Billfath University Indonesian Language Education study program students. The research data is in survey results and interviews with Indonesian Language Education students. The results of surveys and interviews found that the biggest problems in online learning, namely: unstable internet networks and data packages used by students. These two problems ultimately impact the level of understanding of the material by students. In addition, online learning also impacts the ability of mobile phones to respond to data. The memory capacity of mobile phones certainly causes this has exceeded, thus hampering students in learning. Therefore, mutual agreement is needed between students and lecturers so that lecture activities can run smoothly and achieve the lecture's objectives.